2004
DOI: 10.1044/1092-4388(2004/016)
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Representations in Children With SLI

Abstract: The present research examined the quality of the phonological representations of French children with specific language impairment (SLI) and those with normal language development (NLD). Twenty-five children with SLI and 50 children with NLD matched on lexical age level participated in an auditory lexical decision task. The observations gathered in our study can be summarized as follows. First, children with a higher receptive lexical level performed better, and this was true both for children with NLD and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 27 publications
2
36
0
10
Order By: Relevance
“…French (Leclercq, Maillart, & Majerus, 2013;Maillart, Schelstraete, & Hupet, 2004;Pizzioli & Schelstraete, 2011) may not be sensitive enough to reveal the more complex qualitative differences between the groups in the richness of lexical phonological representations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…French (Leclercq, Maillart, & Majerus, 2013;Maillart, Schelstraete, & Hupet, 2004;Pizzioli & Schelstraete, 2011) may not be sensitive enough to reveal the more complex qualitative differences between the groups in the richness of lexical phonological representations.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, given the difficulties children with SLI have in developing abstract phonological representations and accessing phonological representations in memory in comparison to vocabulary-matched children (Claessen & Leitão, 2012;Claessen et al, 2013;Maillart et al, 2004), they might rely more heavily than their peers on sublexical processes when performing lexical decision tasks. Young children's sensitivity to phonotactic probability is generally considered to be derived from bottom-up processing of speech, particularly since their lexicon only provides limited knowledge to extract words from speech (Cutler,1996;Jusczyk, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1 The building process of these representations is still not completely understood, especially for children with Specific Language Impairment (SLI). 2 Although different factors may explain the difficulties with phonological representations observed in children with SLI, authors have suggested that these deficits might be related to the quality of these representations. The representations of children with SLI would be more holistic, similarly to representations of younger children with typical language development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have used other types of tasks to investigate the phonological representations in children, such as naming5,6,7, gating paradigm 8,9 and lexical decision task. 2,10 Considering the abovementioned literature facts, this study was based on the study Phonological Representations in Children with SLI: A study of French 2. The purpose of the study was to analyze the abilities of typically developing children and children with SLI to distinguish words from nonwords in a lexical decision task.…”
Section: Introductionmentioning
confidence: 99%
“…Turning to word recognition and lexical representations, Maillart and colleagues (Maillart, Schelstraete, & Hupet, 2004) provide evidence that recognition by children with SLI is affected by the quality of lexical representations. Children completed a lexical decision task where they were asked to identify auditorially presented stimuli as real words or nonwords.…”
Section: -Developing Lexicon 12mentioning
confidence: 99%